The Neuro-Ophthalmic Features Corresponding with Brain Tumors - Arifuzzaman, A B M; Das, Polak Kumar; Al Azad, Md Alauddin; Mahfujullah, Md; Mustafa, Rashed; Khan, Md Rashed; Ferdous, Baikaly (KYAMC Journal, 2025)
Background: Brain tumor causes several features due to mass effect, irritation, raised intracranial pressure and influence of hormones. The visual pathway and ocular nerves also affected and exerts some neuro-ophthalmic features which might indicate the progress and prognosis of the disease. Objectives: To observe the presentation of neuro-ophthalmic features of brain tumors. Materials and Methods: This cross sectional study was conducted at the department of Ophthalmology and Neurosurgery at Dhaka Medical College and Hospital for twelve months. A total of 100 patients with newly diagnosed brain tumor either by computerized tomography (CT) or magnetic resonance imaging (MRI) were included in this study according to inclusion and exclusion criteria. Results: Mean age of the studied patients was 44.64±10.6 (SD) years. Male 60% and female 40% . Impaired visual acuity was observed in 68% of patients where 19% were blind. Common ocular symptoms were blurring of vision (82%) and impaired color vision (45%) and common neuro-ophthalmic features were headache (84%) papilloedema (48%), optic atrophy (43%), relative afferent pupillary defect (42%), ocular nerve palsy (27%), diplopia (15%), ptosis (4%), and proptosis(6%). The prime location of the tumors were frontal lobe (22%), parietal lobe (21%) and temporal region (19%). The lesions were glioma (29%), meningioma (25%), secondary brain tumor (23%), pituitaryadenoma (7%), craniopharyngioma (5%), vestibular schwannoma (3%), haemangioblastoma (2%), choroid plexus tumor (2%), medullablastoma (2%) and thalamic tumor (2%). Conclusion: In this study, significant numbers of patients were visually impaired at presentation. KYAMC Journal Vol. 16, No. 01, April 2025: 20-23